Analysis of the attitudes of generation z prospective science teachers toward the chemistry virtual laboratory - Qudratuddarsi, Hilman; Rahmah, Nur; Indriyanti, Nor; Jumriani; Munawwarah (Universitas Papua, Manokwari, Indonesia, 2025)
Virtual laboratories are technological innovations that allow users to conduct chemistry experiments interactively without space, time, or material constraints. This study aims to analyze the attitudes of Generation Z prospective science teachers toward using virtual laboratories in chemistry learning by integrating the Theory of Planned Behaviour (TPB) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). A quantitative survey method was applied, involving 83 student respondents. The instrument was a questionnaire that measured performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, attitude, perceived behavioral control, and behavioral intention. The findings revealed a significant positive correlation between all independent variables, behavioral intention, and virtual laboratory usage. Habit and perceived behavioral control emerged as the most influential factors. This study provides valuable insights for developing strategies to integrate virtual laboratories into science teacher education based on Generation Z’s technological preferences.